Synergistic activation of p53 by inhibition of MDM2 expression and DNA damage - Chen, Lihong (National Academy of Sciences, 1998)
The MDM2 oncogene encodes an inhibitor of the p53 tumor suppressor protein that regulates p53 in a negative feedback loop. MDM2 gene amplification and overexpression occur in several types of tumors and are often associated with poor prognosis. An MDM2 antisense phosphorothioate oligodeoxynucleotide has been identified that effectively inhibits MDM2 expression in tumor cells containing MDM2 gene amplifications. Antisense inhibition of MDM2 is associated with a decrease in MDM2–p53 complex formation, increase in p53-inducible gene expression, increase in p53 transcriptional activity, and apoptosis. Significantly, inhibition of MDM2 expression enhances the activation of p53 by a DNA-damaging cancer chemotherapy agent in a synergistic fashion. Therefore, the MDM2 negative feedback pathway is an important limiting factor in DNA damage-induced p53 activation. MDM2 antisense oligonucleotides may be useful as antitumor agents alone or as enhancers of other conventional DNA-damaging drugs.